Collection of 500 Luohansu at Daedeok Temple in Southern Song Dynasty of China - Xiao Mingge (International Journal of Advanced Culture Technology(IJACT), 2025)
The Five Hundred Arhats housed in Daitoku-ji Temple is a significant set of Buddhist paintings from the Southern Song Dynasty, showcasing profound cultural connotations and exceptional artistic techniques. This work vividly portrays the Buddhist narrative of the Five Hundred Arhats, reflecting the religious beliefs and social life of the era, and holds immense research and artistic value. However, due to historical circumstances, some paintings were lost or fragmented during their circulation. This study examines the artistic style, creators, and transmission history of The Five Hundred Arhats through the analysis of historical documents and visual references, offering fresh perspectives on the religious and cultural landscape of the Southern Song Dynasty. In order to trace the origins of Buddhist cultural beliefs, this thesis emphasizes the importance of considering the creative transmission process of these paintings. Thus, a systematic analysis of their stylistic characteristics, authorship, and historical dissemination is conducted.